Simulation and Modelling of Electrical Insulation Weaknesses in Electrical Equipment 2018
DOI: 10.5772/intechopen.79090
|View full text |Cite
|
Sign up to set email alerts
|

Typical Internal Defects of Gas-Insulated Switchgear and Partial Discharge Characteristics

Abstract: Gas-insulated switchgear (GIS) is a common electrical equipment, which uses sulfur hexafluoride (SF 6) as insulating medium instead of traditional air. It has good reliability and flexibility. However, GIS may have internal defects and partial discharge (PD) is then induced. PD will cause great harm to GIS and power system. Therefore, it is of great importance to study the intrinsic characteristics and detection of PD for online monitoring. In this chapter, typical internal defects of GIS and the PD characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Gas insulated apparatus has a complex structure that internal defects may happen during the processes of manufacturing, transferring, and installing [29]. The worldwide in‐service experiences have shown that the main defects in GIS/GIL are metal pollution on spacer surface, metal protrusion on electrode, free metal particles, spacer void and loose shields lead to floating electrode defect, as shown in Fig.…”
Section: Pd Detection With Optical Methodsmentioning
confidence: 99%
“…Gas insulated apparatus has a complex structure that internal defects may happen during the processes of manufacturing, transferring, and installing [29]. The worldwide in‐service experiences have shown that the main defects in GIS/GIL are metal pollution on spacer surface, metal protrusion on electrode, free metal particles, spacer void and loose shields lead to floating electrode defect, as shown in Fig.…”
Section: Pd Detection With Optical Methodsmentioning
confidence: 99%
“…They can provide conductive local path and localized arcing which, in turn, would decrease the dielectric strength between high voltage conductor and outer enclosure. Factors like number of free particles, their size and shape, location (in vicinity of high/low field gradient) represent severity of PD pulses and their detectability [79]. The behavior of floating metals inside the GIS is similar to the corona discharge, in which case charges will accumulate at the sharp spots of the particle and PD would happen due to the electric field enhancement [80].…”
Section: ) Free-moving Metallic Particlesmentioning
confidence: 99%
“…However, GISs have internal defects during manufacture, transportation, and assembly [2]. In GISs, partial discharges (PDs) are not only the precursors of potential internal defects but also lead to gradual deterioration of insulation and ultimately break down or lead to surface discharge [3], [4]. Therefore, PD detection and diagnosis for GISs are required to ensure the safety and the reliability of power grid assets [5].…”
Section: Introductionmentioning
confidence: 99%